Examining grammatical knowledge of English language student teachers - Reimannová, Irena (University of Hradec Králové, 2019)
It is widely believed that the content knowledge, or scholarship in content disciplines, plays the central role in the knowledge base of teaching (Shulman, “Those Who Understand” 6). However, investigations of its acquisition remain rare not only in the context of the Czech Republic, but worldwide (Píšová and Brebera 75). The paper focuses on exploring what role the pre-service education plays in the development of (subject matter) content knowledge of English for Education students, i.e. whether and how the (subject matter) content knowledge of the bachelor programme students of English for Education, namely their grammatical knowledge in English, is developed and internalized in formal education. Based on the analysis of tests and examination scores of English for Education students, the study hypothesizes that there is correlation between the selected aspects of communicative competence in the course of the studies, i.e. there is a (positive) change. However, drawing on correlations of exam scores in students’ grammatical knowledge, namely results of morphology exam assessments and a grammatical part of the language exam, it does not seem that by addressing the processes of grammar learning and acquisition in the formal instruction, student teachers improve their conscious use of grammar.
Zkoumání úrovně gramatické znalosti studentů učitelství anglického jazyka
Keywords: grammatical knowledge; english language; student teachers; gramatická znalost; studenti učitelství; anglický jazyk